Creating space for learner autonomy: an interactional perspective. Issue 2 (4th May 2017) - Szczepek Reed, Beatrice
Abstract: This paper is concerned with teachers' and learners' collaborative pursuit of learner autonomy in a highly asymmetrical education setting, the music masterclass. Evaluations are identified as a potential opportunity for the mutual construction of learner autonomy. The analysis shows that, while teaching professionals mitigate interactional inequalities and thus reflexively handle asymmetrical interaction, words alone do not address the imbalances that exist. It is only when teachers show determination in pursuing invitations for students to engage and provide sequential slots for them to do so that spaces for learner autonomy are created. Students are also shown to take charge of their own learning by evaluating themselves, rather than waiting for teachers to do so. The data show that, while interactional asymmetries can be deeply ingrained in traditional forms of instruction, the local co-construction of social life means that patterns of instruction can be negotiated in situ rather than being the inevitable result of established hierarchies. However, doing so requires considerable interactional effort.